Adult Recurrent Tonsillitis : Infection, Immune Dynamics, and Holistic Primary Care - Dasa Novita, Khuznita; Rosita, Rita; Istiqomah, Rosyida (Jurnal Ilmu Kedokteran Keluarga, 2025)
Chronic tonsillitis, a frequent recurring inflammation of the pharynx, profoundly affects quality of life. Tonsils, which are important immune organs, are constantly exposed to germs. A long-lasting infection can cause chronic inflammation and lead to structural changes in the body, which is why family medicine needs to take a comprehensive approach. A 35-year-old male exhibited recurrent pharyngitis, T4 tonsil hypertrophy, and persistent snoring. This shows how much his condition affects his body, since he has had many episodes that have affected his daily life. A microbial infection, typically bacterial or viral, causes recurrent tonsillitis, accompanied by an immune response that isn't functioning properly in the tonsillar crypts. This causes long-term swelling and blockage of the airways, which can make it hard to breathe and snore. Lifestyle factors that make you more likely to get sick, like your diet and smoking history, make this worse. A comprehensive family medicine evaluation, encompassing biomedical, psychosocial, and environmental factors, informs individualized management that targets infectious agents, immune function, and physiological health. This method, which focuses on infectious causes, immune responses, and physical effects, is crucial for achieving good results and maintaining health in individuals with chronic tonsillitis.